'Diet and lifestyle' in the management of dyslipidaemia and prevention of CVD - Understanding the level of knowledge and interest of European Atherosclerosis Society members. (December 2020) - Trautwein, Elke A.; Catapano, Alberico L.; Tokgözoğlu, Lale
Abstract: To better understand the level of knowledge and interest in 'diet and lifestyle' for cholesterol management and CVD prevention, European Atherosclerosis Society (EAS) members were invited to take part in an online survey. In total, 269 EAS members participated of which 64 (24%) were students/postdocs, 102 (38%) researchers involved with CVD-related research and 103 (38%) doctors and clinicians who directly interact with patients. All (99%) of the participants either agreed or strongly agreed that 'diet and lifestyle' have a role to play in cholesterol management, with 80% indicating that 'diet and lifestyle' is very or extremely important. Of the clinicians, 75% indicated that their patients voluntarily ask for 'diet and lifestyle' advice and over 80% said they continuously provide 'diet and lifestyle advice' to their patients. Of the surveyed clinicians, 91% feel sufficiently educated and confident to provide expert advice and over 90% recommend medication, diet change, frequent exercise and smoking cessation to their patients. In view of more specific dietary advice, clinicians reportedly recommend a 'Mediterranean diet', and advise to avoid high-fat foods, and to increase intake of high-fibre foods. Interestingly, smoking cessation and alcohol avoidance were mentioned less frequently. In view of educational needs, over half of the surveyed EAS members use the internet and 'guidelines' to learn about 'diet and lifestyle' in relation to cholesterol and CVD risk management. Clinicians tend to use 'guidelines' more often, while students/postdocs tend to use the internet significantly more than clinicians and CVD researchers. Regarding unmet needs for educational tools addressing specifically 'diet and lifestyle', clinicians feel that patient-oriented leaflets and pocket guidelines would be most beneficial materials to introduce, while students/postdocs would prefer an app. In summary, the role of 'diet and lifestyle' as a cornerstone of cholesterol management and CVD risk prevention seems well recognised amongst EAS members surveyed. Graphical abstract: Image 1 Highlights: An online survey evaluated the knowledge in 'diet and lifestyle' for CVD prevention. EAS members took part in this online survey. Most participants indicated that 'diet and lifestyle' is very or extremely important. They declared to use internet and guidelines to learn about 'diet and lifestyle'. The role of diet and lifestyle as a cornerstone for CVD prevention seems recognised.